Aflatoxin Contamination of Livestock Feeds and Feed Ingredients in Andhra Pradesh - T.Mohanamba; M.Vasundhara Priyanka; L.Ratna Kumari; R.Amarendra Kumar (The Indian Veterinary Journal, 2024)
An attempt was made to study the aflatoxin contamination of compound livestock feeds and feed ingredients in Andhra Pradesh during the year 2023-24. Aflatoxin estimation was made by AOAC methods. Among the compound livestock feeds tested, highest incidence was noticed in cattle feeds followed poultry feeds. Analysis of feed ingredients revealed highest incidence in groundnut cake followed by maize.